Satisfaction Assessment of the Quality of Life of Urban Families and their Roles in the Development of Zabol - Farnam, Javad; Miri, Gholam Reza; Rezazade, Mahsume Hafez (International Journal of Geography and Geology, 2015)
Urban growth and urbanization is the most prominent feature of socio-economic developments in recent times. Therefore, along with urbanizing of the society of Iran, analysis of its consequences, including the assessment of the quality of urban life is one of the most important needs of urban studies. Accordingly, this study analyze the satisfaction of quality urban life and its role in the development of the city of Zabol. The kind of the research is applied research and its method is descriptive-analytic based on questionnaire. The statistical community is residents of the city of Zabol and the sample community are 195 people living in five districts of Zabol. The sampling method is randomly and sample size has been calculated by the Cochran method. Data and Information have been analyzed by statistical Methods of SPSS software. The overall results showed that the citizens' satisfaction with the quality of life in the city of Zabol with 2/46 of average value is less than average. The social dimension with average value of 2/67 and the Physical environmental dimension with average value of 2/33 have allocated the highest and the lowest of the citizens’ satisfaction with the quality of life respectively.